TINDAK TUTUR DIREKTIF DAN STRATEGI BERTUTUR GURU DALAM PEMBELAJARAN BAHASA INDONESIA DI KELAS XII SEKOLAH INTERNASIONAL MONDIAL BATAM - Raihan Abyzar; Farel Olva Zuve (EDU RESEARCH, 2024)
The phenomenon of learning communication in international classrooms has its own complexity, especially in the use of directive speech acts and teachers' speech strategies. At Mondial International School Batam, the diversity of students' cultural and linguistic backgrounds creates challenges in delivering learning instructions. This study aims to identify and analyze the form of directive speech acts and teachers' speech strategies in learning Indonesian in class XII. Through a qualitative approach with descriptive method, data were collected using the free listening technique (SBLC) of Indonesian teachers' speech, with validation using triangulation of data, investigators, and theories. Data analysis revealed five forms of directive speech acts: ordering (52 utterances), pleading (4 utterances), demanding (49 utterances), suggesting (31 utterances), and challenging (11 utterances). The dominant speech strategy is Straightforward Speech with Positive Politeness (67 utterances), followed by Straightforward Speech without Politeness (63 utterances), Negative Politeness (16 utterances), and Vague Speech (1 utterance). This communication pattern shows the tendency of teachers to use directive speech acts of ordering with positive politeness strategies to create a conducive and inclusive learning atmosphere, while maintaining respectful relationships with students in the context of an international classroom.